2018
DOI: 10.1007/s13361-018-1893-2
|View full text |Cite
|
Sign up to set email alerts
|

Direct Analysis of Proteins from Solutions with High Salt Concentration Using Laser Electrospray Mass Spectrometry

Abstract: The detection of lysozyme, or a mixture of lysozyme, cytochrome c, and myoglobin, from solutions with varying salt concentrations (0.1 to 250 mM NaCl) is compared using laser electrospray mass spectrometry (LEMS) and electrospray ionization-mass spectrometry (ESI-MS). Protonated protein peaks were observed up to a concentration of 250 mM NaCl in the case of LEMS. In the case of ESI-MS, a protein solution with salt concentration > 0.5 mM resulted in predominantly salt-adducted features, with suppression of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The observation of the sodium and potassium adducts is very common in ESI-MS spectra, possible due to background impurities and to the considerable presence, in some cases, of ionic medium NaCl in solution [32]. Furthermore, an intensity decrease of the [ H ( L5 ) + H] + peak with ionic strength increase was noticed, in particular at I = 1.00 mol L −1 , due to a signal suppression attributable to the ionic medium effect, leading to a significant salt-adducted species formation [33,34,35].…”
Section: Resultsmentioning
confidence: 99%
“…The observation of the sodium and potassium adducts is very common in ESI-MS spectra, possible due to background impurities and to the considerable presence, in some cases, of ionic medium NaCl in solution [32]. Furthermore, an intensity decrease of the [ H ( L5 ) + H] + peak with ionic strength increase was noticed, in particular at I = 1.00 mol L −1 , due to a signal suppression attributable to the ionic medium effect, leading to a significant salt-adducted species formation [33,34,35].…”
Section: Resultsmentioning
confidence: 99%
“…Matrix-assisted laser desorption/ionization (MALDI) has been limited for native MS because it typically uses denaturing sample preparation conditions such as organic matrices and drying, requiring covalent cross-linking to stabilize noncovalent complexes for analysis . Recently, studies have demonstrated the capability for MALDI to preserve noncovalent interactions for proteins using liquid matrices. , Other laser-based methods that have been shown to preserve native-like protein features include desorption by impulsive vibrational excitation (DIVE) and laser electrospray ionization (LEMS), but these techniques have not been applied to membrane proteins to our knowledge.…”
Section: Ionization: From Solution Into the Gas Phasementioning
confidence: 99%
“…A more recent development, ambient ionization, pioneered with the development of desorption ionization mass spectrometry (DESI), has been shown to tolerate highly complex samples without a chromatographic separation due to the unique sample introduction and ionization mechanism of the technique . This development impelled various ambient ionization techniques to include electrospray laser desorption ionization (ELDI), laser ablation electrospray ionization (LAESI), and laser electrospray mass spectrometry (LEMS), which have all demonstrated high tolerance for complex samples without separation or sample preparation. It should be noted that these techniques are just beginning extensive validation investigations and considerable research is needed to confirm their abilities to identify and quantitate trace level analytes from complex biological samples without sample preparation or separation.…”
Section: Introductionmentioning
confidence: 99%